2015
DOI: 10.4274/meandros.2241
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Indices in Patients with Preeclampsia

Abstract: Objective: The purpose of study was to investigate erythrocyte indices in patients with preeclampsia. Materials and Methods:The study population consisted of 102 patients with preeclampsia (49 mild, 53 severe preeclampsia) and 98 control pregnant patients. For the entire study population, red blood cell indices, including baseline mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), red cell distribution width (RDW), and red blood cell (RBC) were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
3
6
1
Order By: Relevance
“…Increasing neutrophils are associated with increasing inflammation and on the other hand low levels of lymphocytes are associated with poor general health, increasing cortisol levels, and increasing level of apoptosis due to stressor [1,4,8]. Unfortunately, we did not find any significant difference of NTR between early and late onset of preeclampsia.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Increasing neutrophils are associated with increasing inflammation and on the other hand low levels of lymphocytes are associated with poor general health, increasing cortisol levels, and increasing level of apoptosis due to stressor [1,4,8]. Unfortunately, we did not find any significant difference of NTR between early and late onset of preeclampsia.…”
Section: Discussioncontrasting
confidence: 70%
“…This was in accordance with other previous research. Several previous studies concluded that NTR has a prognostic value to predict diseases such as malignancy, coronary heart disease, and preeclampsia [1,4]. Oylumlu et al presented the increase levels of NTR in pregnancy with preeclampsia [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the 11 studies were of high quality with an Ottawa rating of 7 and 8 (Table 1). Of the eligible studies, 5 (45%) [15, 17, 18, 21, 23] and 2(18%) [22, 24] studies were conducted in Turkey and Sudan respectively. One (9%) study each was conducted in China, India, Taiwan and Indonesia.…”
Section: Resultsmentioning
confidence: 99%
“…The number of the cases per study ranged from 21 [35] to 143 [14], while the controls ranged from 50 [23] and 911 [14]. The median and variance was reported in three studies [18, 19, 21] and this was transformed to the mean (SD) using the prescribed formula [29, 30]. The mean (SD) of the RDW level was significantly higher in women with preeclampsia compared to controls [15.10 (2.48) % vs. 14.26(1.71) %, P < 0.001].…”
Section: Resultsmentioning
confidence: 99%